Silencing of C3G increases cardiomyocyte survival inhibition and apoptosis via regulation of p‐ERK1/2 and Bax. (27th September 2018) - Yang, Dongyan; Zhang, Lei; Zhang, Zhisheng; Hu, Sulei; Fu, Yanbo; Laukkanen, Jari A.; Li, Gang
Summary: Experimental studies have shown that overexpression of Rap guanine nucleotide exchange factor 1 (C3G) plays pro‐survival and anti‐apoptotic roles through molecule phosphorylated extracellular signal‐regulated kinase1/2 (p‐ERK1/2) in cardiomyocytes. However, it is still unclear if silencing of C3G may increase cell survival inhibition and apoptosis in cardiomyocytes, and whether C3G silence induced injuries are reduced by the overexpression of C3G through regulation of p‐ERK1/2 and pro‐apoptotic molecule Bax. In this study, the rat‐ derived H9C2 cardiomyocytes were infected with C3G small hairpin RNA interference recombinant lentiviruses, which silenced the endogenous C3G expression in the cardiomyocytes. Then, contrary experiments were conducted using C3G overexpression. The cell proliferation and apoptosis were analyzed in the cardiomyocytes which were treated with or without hypoxia/reoxygenation (H/R). Silencing of C3G leaded to significant increase in cell survival inhibition and apoptosis, combined with aggravated the injuries induced by H/R. Overexpression of C3G reduced the injuries induced by the silencing of C3G in the cardiomyocytes via regulation of p‐ERK1/2 and Bax. In conclusion, our results provide new experimental evidence that silencing of C3G can increase cell survival inhibition and apoptosis in cardiomyocytes via regulation of p‐ERK1/2 and Bax.